A biodegradable system for the tailored delivery of growth factors and its application to bone morphogenetic protein-2 delivery for bone repair - Cox, Helen Celia (2013)
The repair of bone defects and fracture non-unions remain a challenge for clinicians. Current materials have limitations regarding quality, availability and there are long-term complications. Alternative graft materials, often in combination with growth factors have been investigated, but, poor retention of growth factors has lead to the clinical use of high doses and/or frequent injections, putting the patient at risk of adverse effects.